Installation of partition wall (non-load bearing wall) / Muhamad Luqman Al-Hakim Zakaria - Zakaria, Muhamad Luqman Al-Hakim (Universiti Teknologi MARA, Perak, 2021)
Partition walls are one of the most important structures for non-load bearing wall elements of a building. A non-load bearing wall plays several functions in the performance of a house, space and rooms and these functions need to be fully understood in order to create a suitable and comfortable space as well as providing privacy. This report will discuss about the installation of non-load bearing wall which is partition wall of the spaces. This report was conducted for the renovation and modification of director’s room of Teknologi Maklumat dan Rekod (BTMR), ibu pejabat, Jabatan Imigresen Malaysia who is located at Putrajaya. The objective of this report is to analyse the installation of partition wall and the way how it carried out. It will focus on the whole process of the installation the partition walls. This report will also look to at the problem and the solution in installation of partition wall.